Influence of Some Red Fescue (Festuca Rubra L.) Associations and Nitrogen-Based Fertilization on Dry Matter Yield - Corina Cristea; Neculai Dragomir; Teodor Cristea; Carmen Dragomir; Dorin Rechiţean; Sebastian Toth; Iulian Frățilă (Scientific Papers Animal Science and Biotechnologies, 2023)
One of the most efficient measures that contributes to forage improvement is represented by the temporary pastures consisted of legumes and perennial gramineae. Beside Agrostis tenuis, Festuca rubra is the forage gramineae with the largest spread and dominance in our country. That is why its introduction in various associations with forage legumes leads to qualitative and quantitative improvement of the yields obtained on temporary pastures.